Pathways towards a sustainable future envisioned by early‐career conservation researchers. Issue 9 (26th July 2021) - Raatikainen, Kaisa J.; Purhonen, Jenna; Pohjanmies, Tähti; Peura, Maiju; Nieminen, Eini; Mustajärvi, Linda; Helle, Ilona; Shennan‐Farpón, Yara; Ahti, Pauliina A.; Basile, Marco; Bernardo, Nicola; Bertram, Michael G.; et al.
Abstract: Scientists have warned decision‐makers about the severe consequences of the global environmental crisis since the 1970s. Yet ecological degradation continues and little has been done to address climate change. We investigated early‐career conservation researchers' (ECR) perspectives on, and prioritization of, actions furthering sustainability. We conducted a survey ( n  = 67) and an interactive workshop ( n  = 35) for ECR attendees of the 5th European Congress of Conservation Biology (2018). Building on these data and discussions, we identified ongoing and forthcoming advances in conservation science. These include increased transdisciplinarity, science communication, advocacy in conservation, and adoption of a transformation‐oriented social–ecological systems approach to research. The respondents and participants had diverse perspectives on how to achieve sustainability. Reformist actions were emphasized as paving the way for more radical changes in the economic system and societal values linked to the environment and inequality. Our findings suggest that achieving sustainability requires a strategy that (1) incorporates the multiplicity of people's views, (2) places a greater value on nature, and (3) encourages systemic transformation across political, social, educational, and economic realms on multiple levels. We introduce a framework for ECRs to inspire their research and practice within conservation science to achieve real change in protecting biological diversity. Abstract : Single‐targeted sustainability actions need to be tied to a global, more radical systemic change which includes conservation science. We introduce a framework for early‐career researchers and practitioners to inspire their work within conservation science and to create and achieve real change in protecting biodiversity. We hope for further discussion on the multiplicity of ECR views regarding ways to achieve sustainability.